Variations and characteristics in changes of the crater lake level of Irazú volcano (1965-2012), Costa Rica - Ramírez, Ronald (2011)
The small and ephemeral crater lake of the Irazú has presented noticeable changes in its coloring, tem- perature, pH, and depth from 1965 until 2012. The level has varied from 31 m in 1995 and 2001 to stay completely dry in 1977, 1979, 1982-83, 1987 and 1990. These levels are not always directly related to the amount of rainfall. It seems that at times the waterproofed base of the lake was cracked allowing the lake to drain relatively quickly, leaving the base visible for several months or years, and after a time, formed again. The variation of the color (green, turquoise-blue, yellow, rare whitish and reddish), temperature (16o-35oC), and pH (2.85-5.85) seems to be related to the depth, un- derwater fumarolic activity, algae activity and ferruginous sediments produced by the constant landslides of the walls.